The Aftermath of 21st Century Sharia Implementation in Northern Nigeria - Muhammad Duku (Media of Law and Sharia, 2022)
Enforcement of Sharia legal system is a duty bound over every Muslim (Male or Female) on their day to day life and activities. The objective of this paper is to examine the consequences after the implementation of Shari’ah law in 21st Century in Northern part of Nigeria. Therefore, this study addresses the major area of negation and setback in the implementation of Shari’ah law in 21st Century in Northern Nigeria. The study posit out that inconsistence of Nigerian constitution with Shari’ah law, capital offence punishable by Shari’ah law, Hisbah institution, lack of qualified and experts judges, political problem and many others are the setback encountered by means of Shari’ah implementation in Northern Nigeria. Conclusively, the study concludes that 21st Century Shari’ah implementation in Northern Nigeria faced with many challenges.